Thermal Behaviors and Optical Parametric Oscillation in 4H‐Silicon Carbide Integrated Platforms. Issue 10 (5th August 2021) - Shi, Xiaodong; Fan, Weichen; Hansen, Anders Kragh; Chi, Mingjun; Yi, Ailun; Ou, Xin; Rottwitt, Karsten; Ou, Haiyan
Abstract : 4H‐silicon carbide (SiC) integrated platforms have shown great potential in quantum and nonlinear photonics. However, the thermal properties of 4H‐SiC waveguides are still unknown, even though thermo‐optic effects can play an important role in fundamental measurements and practical applications. Herein, the thermo‐optic effects in a 4H‐SiC microring resonator are comprehensively studied, by means of both temperature tuning and self‐heating. The thermo‐optic coefficient and the ratio between the thermal absorption and the thermal diffusion of 4H‐SiC are quantitatively measured to be 4 . 21 × 10 − 5  K − 1 and 14 . 9  K W − 1, respectively. Considering the acquired thermal properties, Kerr‐nonlinearity‐based dual‐pump optical parametric oscillation (OPO) is experimentally achieved, and thus, it is demonstrated that broadband solitons can feasibly be generated through thermal tuning of 4H‐SiC‐on‐insulator (SiCOI) microring resonators. Abstract : The 4H‐silicon carbide (SiC) integrated platform is demonstrating great potentials in nonlinear and quantum photonics. Herein, thermal properties of 4H‐SiC microrings are comprehensively studied. Based on this study, dual‐pump optical parametric oscillation is experimentally generated, and a proof‐of‐principle soliton frequency comb is proposed. These results show an appealing prospect of the 4H‐SiC integrated platform for optical communication, metrology, and spectroscopy.